Effect of growth rate on quality of Alq3 films and Co diffusion. (1st February 2021) - Mondal, Kali Prasanna; Bera, Sambhunath; Gupta, Ajay; Kumar, Dileep; Gome, Anil; Reddy, V Raghavendra; Ito, Nobuaki; Yamada-Takamura, Yukiko; Pandit, Pallavi; Roth, Stephan V
Abstract: The quality of organic semiconductor tris-(8-hydroxyquinoline)aluminum (Alq3 ) thin films, deposited at the rate of 5.0 Å s −1, 2.5 Å s −1, and 1.0 Å s −1 respectively, have been investigated using x-ray reflectivity (XRR) and grazing incidence small angle x-ray scattering (GISAXS) studies. While XRR provides information about structural details, GISAXS provides information about the morphology of the films. The film quality is very good with a surface roughness of only 8 Å. The electron density of the film increases from 0.39 e Å −3 to 0.43 e Å −3 due to reduction of growth rate from 5 Å s −1 to 1 Å s −1 . The higher electron density (0.43 e Å −3 ) of the film deposited at the lower deposition rate (1 Å s −1 ) indicates the presence of less defects and/or porosity in the film. Average separation between pores increases from 200 Å to 500 Å and simultaneously pore depth decreases from 300 Å to 120 Å due to reduction of growth rate from 5 Å s −1 to 1 Å s −1 . The mixing between Alq3 and Co at the Alq3 /Co interface and diffusion of Co into Alq3 layer through Co/Alq3 interface have been studied by combined XRR and grazing incidence x-ray standing wave (GIXSW) measurements for the three Alq3 /Co/Alq3 /W/Si multilayers in which Alq3 films were deposited at the above mentioned three different rates. It is found that there is about 30 Å thick (∼ two monolayer of Alq3 ) mixing region at the Alq3 /Co interface in three multilayer samples, which suggests that mixing at this interface is independent of the growth rate of Alq3 films. The depth of diffusion of Co into Alq3 through Co/Alq3 interface reduces from 300 Å to 160 Å due to the reduction of deposition rate from 5 Å s −1 to 1 Å s −1 . This study suggests that by controlling the growth rate of Alq3, porosity as well as the diffusion of ferromagnetic Co in an organic semiconductor Alq3 can be reduced, which plays an important role in the performance of organic spin valve devices.